Палеоботанічні дослідження з пам’яток слов’янських культур. Каталог - Пашкевич, Г.О.; Горбаненко, С.А. (Археологія і давня історія України, 2010)
Науковому загалу запропоновано детальну та повну інформацію про дослідження з палеоетноботаніки у галузі ранньослов’янскьої археології. Каталог пам’яток з дослідженими ПБС є інформативним виданням без інтерпретації матеріалу. Предложена подробная и полная информация об исследованиях палеоэтноботанических материалов раннеславянских памятников. Каталог памятников с исследованными ПБС является информативным изданием без интерпретации материала. В каталог включены материалы археологических культур, признанных в археологической литературе раннеславянскими — зарубинецкая культура и позднезарубинецкие памятники, зубрицкая и пшеворская культуры в Украине, поенешти-лукашевская, липицкая культуры конца І тыс. до н. э. — І тыс. н. э.; киевская, черняховская культуры, культура карпатских курганов, вельбарская культура второй четверти І тыс.; пеньковская, пражская, колочинская культуры третьей четверти І тыс.; райковецкая, волынцевско-роменская культуры последней четверти І тыс. The detailed and comprehensive information on the researched palaeobotanic materials of the Early Slavic sites is presented here. Catalogue of the monuments where the palaeobotanic spectrum is researched is an informative publication without the interpretation of materials. It includes the materials of archaeological cultures recognised in the archaeological literature as the Early Slavic: Zarubynetska culture and the Late Zarubynetska monuments, Zubrytska and Pshevorska cultures in Ukraine, Poyaneshty-Lukashivska, Lypytska cultures from the end of the 1st millennium BC to the 1st millennium AD; Kyiv and Chernyakhivska cultures, Carpathian Barrows and Velbarska culture of the second quarter of the 1st millennium; Penkivska, Prazhska, and Kolochynska cultures of the third quarter of the 1st millennium; Raykovetska and Volyntsevsko-Romenska cultures of the last quarter of the 1st millennium.